Sublingual protein delivery by a mucoadhesive patch made of natural polymers. (1st July 2021) - Paris, Anne-Lise; Caridade, Sofia; Colomb, Evelyne; Bellina, Mélanie; Boucard, Eléa; Verrier, Bernard; Monge, Claire
Abstract: The sublingual mucosa is an appealing route for drug administration. However, in the context of increased use of therapeutic proteins, development of protein delivery systems that will protect the protein bioactivity is needed. As proteins are fragile and complex molecules, current sublingual formulations of proteins are in liquid dosage. Yet, protein dilution and short residence time at the sublingual mucosa are the main barriers for the control of the dose that is delivered. In this work, a simple delivery scaffold based on the assembly of two polysaccharides, chitosan and hyaluronic acid, is presented. The natural polymers were assembled by the Layer-by-Layer methodology to produce a mucoadhesive and oro-dispersible freestanding membrane, shown to be innocuous for epithelial human cells. The functionalization of the membrane with proteins led to the production of a bioactive patch with efficient loading and release of proteins, and suitable mechanical properties for manipulation. Sublingual administration of the patch in mouse evidenced the absence of inflammation and an extended time of contact between the model protein ovalbumin and the mucosa compared to liquid formulation. The delivery of fluorescent ovalbumin in mouse sublingual mucosa demonstrated the penetration of the protein in the epithelium 10 min after the patch administration. Moreover, a migration assay with a chemokine incorporated into the patch showed no decrease in bioactivity of the loaded protein after enzymatic release. This study therefore provides a promising strategy to develop a sublingual protein delivery system. Statement of significance: Although the oral route is largely used for drug delivery, it has limitations for the delivery of proteins that can be degraded by pH or gastric enzymes. The sublingual route therefore appears as an interesting approach for protein administration. In this work, a simple delivery scaffold is presented based on the assembly of two polysaccharides by the Layer-by-Layer methodology to produce a mucoadhesive patch. The produced patch allowed efficient loading and release of proteins, as well as protection of their bioactivity. An extended time of contact between the protein and the mucosa compared to liquid formulation was highlighted in mouse model. This study provides a promising strategy to develop a sublingual protein delivery system. Graphical abstract: Image, graphical abstract